IJCM_240A: A cross sectional study to assess the health literacy among adults attending outpatient clinics at a government tertiary care hospital in urban Bangalore. - Jayarajan Vishnu; Jadhav Jyothi; Ranganath TS (Indian Journal of Community Medicine, 2024)
Background: WHO defines health literacy as cognitive and social skills that determine the motivation and ability of people to understand, gain access and use the information to obtain good health. Inadequate health literacy has been linked to increased hospital admissions, poorer physical and mental health, lower use of preventive health services like vaccinations and screening tests. These ultimately lead to higher healthcare costs. This study was conducted to assess health literacy among adults attending outpatient clinics at a government tertiary care hospital in urban Bangalore. Objectives: To estimate proportion of inadequate health literacy and its associated factors among adults attending outpatient clinics at a government tertiary care hospital in urban Bangalore. Methodology: A cross-sectional study was conducted among adult attendees (i.e., patients and companions) of outpatient clinics of a government tertiary care hospital in urban Bangalore. Based on a study done by Almaleh. R et al. (P = 34.3%) with 7% absolute precision, the sample size was calculated as 200. A total of 200 adults attending outpatient clinics at the government tertiary care hospital were selected using simple random sampling. Data was collected using a pre-tested, semi-structured questionnaire for sociodemographic factors and HLS-EU-Q16 (European Health Literacy Survey Questionnaire short version) for assessing health literacy. The data collected was entered in MS Excel and analysed using SPSS 21.0. Results: The proportion of inadequate health literacy among study participants was observed to be 38%. Factors like educational status, age, and gender were found to have an association with it. Health literacy was found to be least in lower-educated individuals. Conclusion: From the present study, it was found that a large part of adult population had limited health literacy. It should be addressed through proper interventions, like ensuring basic education and health awareness programmes.